Orthogonal sets and polar methods in linear algebra : Applications to matrix calculations, systems of equations, inequalities, and linear programming - Castillo, Enrique; Cobo, Angel; Jubete, Francisco (New York : Chichester : John Wiley and Sons, INC, 1999)
This is a first-year graduate text on linear algebra for applications. Castillo makes a great effort at connecting physical and mathematical realities, showing the reader the reasons that lead to the analysis of structures and concepts
Includes bibliographical references and index.
Keywords: Algebras, Linear; Orthogonalization methods